PERAN KELOMPOK TANI DAN KAPASITAS PETANI DALAM PENGENDALIAN HAMA TERPADU (PHT) DI DESA WAWOONE KECAMATAN WAWONII SELATAN KABUPATEN KONAWE KEPULAUAN - Khairul Khatima; Awaluddin Hamzah; Yoenita Jayadisastra; Yani Taufik (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
The objective of this study is to ascertain the role of farmer groups and the capacity of wetland rice farmers in Integrated Pest Management (IPM). The population of this study comprised 27 individuals who engaged in wet-rice farming and were members of the farmer group in Wawoone Village. The research sample was determined using the census method. The data were collected using survey techniques, documentation, and interviews with the use of questionnaires. The present study will investigate the role of farmer groups and the capacity of wetland rice farmers. The results demonstrated that the role of farmer groups and the capacity of wet-rice farmers in Integrated Pest Management (IPM) in Wawoone Village, South Wawonii District, Konawe Islands Regency have each been implemented quite well. A close relationship is exhibited by the role of farmer groups and the capacity of wet-rice farmers in Integrated Pest Management (IPM) in Wawoone Village, as evidenced by a correlation coefficient value of 0.774. The efficacy of farmer groups is directly correlated with the capacity of wet-rice farmers to implement IPM.